KARAKTERISTIK DAN BANGKITAN PERJALANAN ZONA TERHADAP PUSAT PERBELANJAAN (STUDI KASUS : MALL OF SERANG DI KOTA SERANG) - , DWI ESTI INTARI; , Prof. Ir. Sigit Priyanto. M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In the term of a cityâs growth, the emergence of various modern shopping centers or malls becomes something with the most prominent and rapid growth. In the Serang , there are at least two modern shopping centers (mall). One of them is the Mall of Serang. Mall is a activity center that can cause a movement generation of a zone. In line with the existence of the Mall of Serang, it is predicted to cause the people of Serang and out of city movement activity to increase in term of need fulfillment or in other words, the increase on the number of zone movement toward the Mall of Serang. This research is aimed at finding out the characteristic and number of trip generation from a zone to the Mall of Serang. The method used in this research is the survey done by filling questionnaire by the 416 respondents from the two movement zone, the internal and external zone. The result of the questionnaire is then tabulated and analyzed using the cross-classification analysis. The result of this study shows that the number of trip generation occurring is 318 household from the internal zone having trips/ day. Whereas from the external zone the number of trip generation is 91 household having trips/ day. So the total number of trip generation in zone toward the Mall of Serang is 409 trips/day. Based on the number of trip generation in zone, it can be predicted that the number of transportation mode used to go to the Mall of Serang, which consists of cars with 82 known movements, motorcycles with 237 movements, public transportation with 78 movements and pedestrians and non-motor vehicle with 8 movements.